SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KETUA GP ANSOR PAC KLANGENAN DENGAN METODE PROFILE MATCHING - Rohman, Fatkhurohman (Kohesi: Jurnal Sains dan Teknologi, 2023)
Youth and community organizations play an important role in promoting social and religious activities at the local level. In Cirebon Regency, the Klangenan Branch of Ansor Youth Movement (GP), as part of Nahdlatul Ulama (NU), carries out various routine activities and religious celebrations. One of the most important aspects in this organization is the election of the chairman, who has a great influence on the direction and progress of the activities. However, the determination of the chairman of GP Ansor PAC Klangenan still faces challenges in evaluating and selecting the chairman candidate that best suits the needs and characteristics of the organization. The method used in this paper is profile matching using the criteria of leadership, honesty, communication, empathy, religious knowledge, emotional intelligence and organization. Then, the comparison between the candidate's profile and the expected profile is processed and a ranking of candidates is made based on the calculated competency differences. By using this system, it is expected that the process of determining the Chairman of GP Ansor PAC Klangenan will be more structured, objective and efficient. The criteria established in the system will help to ensure that candidates for the chairmanship are selected on the basis of competencies and character in line with the needs of the organization. The results of this study can provide guidance for a better decision-making process in determining the chairman of GP Ansor PAC Klangenan. Keywords: DSS, Profile Matching, Youth Organization, Nahdlatul Ulama